2019
DOI: 10.1101/759852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitylated H2A.Z nucleosomes are associated with nuclear architectural proteins and global transcriptional silencing

Abstract: H2A.Z mono-ubiquitylation has been linked to transcriptional repression, but the mechanisms associated with this process are not well understood due to the lack of reagents specific for this modified form of H2A.Z. To address this, we developed a biotinylation-based approach to specifically purify ubiquitylated H2A.Z (H2A.Zub) mononucleosomes and characterize their biochemical composition and genomic distribution. We observe that H2A.Zub nucleosomes are enriched for the repressive histone post-translational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…For example, it has been demonstrated that H2A.Z and H3.3 containing mononucleosomes are enriched for activating histone PTMs such as K4 methylated H3 (Viens et al, 2006;Sarcinella et al, 2007;Won et al, 2015), whereas macroH2A containing mononucleosomes are enriched for repressive histone PTMs like K9 methylated H3 (Won et al, 2015). In addition, this method has also been used to dissect the cross-talk between macroH2A1 and H2B acetylation (Chen et al, 2014;Ruiz and Gamble, 2018), and H2A.Z ubiquitylation with H3K27me3 (Ku et al, 2012;Surface et al, 2016;Ng et al, 2019). Lastly, the incorporation of specific core or variant histones into chromatin has been demonstrated by the nucleosome-immunoprecipitation method (Kanda et al, 1998;Wiedemann et al, 2010;Lau et al, 2011;Ruiz and Gamble, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that H2A.Z and H3.3 containing mononucleosomes are enriched for activating histone PTMs such as K4 methylated H3 (Viens et al, 2006;Sarcinella et al, 2007;Won et al, 2015), whereas macroH2A containing mononucleosomes are enriched for repressive histone PTMs like K9 methylated H3 (Won et al, 2015). In addition, this method has also been used to dissect the cross-talk between macroH2A1 and H2B acetylation (Chen et al, 2014;Ruiz and Gamble, 2018), and H2A.Z ubiquitylation with H3K27me3 (Ku et al, 2012;Surface et al, 2016;Ng et al, 2019). Lastly, the incorporation of specific core or variant histones into chromatin has been demonstrated by the nucleosome-immunoprecipitation method (Kanda et al, 1998;Wiedemann et al, 2010;Lau et al, 2011;Ruiz and Gamble, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…H2A.Z is also located at centromeres and, in mouse trophoblast stem cells, its abundance at centromeres fluctuates, such that the highest concentration occurs at mitosis when it is required for chromosome segregation [ 82 ]. Monoubiquitylation of H2A.Z is also associated with heterochromatin [ 85 ].…”
Section: Heterochromatin Formation By H2azmentioning
confidence: 99%